Gait Phase Subdivision and Leg Stiffness Estimation During Stair Climbing - Teng Ma; Jiale Zhu; Kuangen Zhang; Wentao Xiao; Haiyuan Liu; Yuquan Leng; Haoyong Yu; Chenglong Fu (IEEE, 2022)
Leg stiffness is considered a prevalent parameter used in data analysis of leg locomotion during different gaits, such as walking, running, and hopping. Quantification of the change in support leg stiffness during stair ascent and descent will enhance our understanding of complex stair climbing gait dynamics. The purpose of this study is to investigate a methodology to estimate leg stiffness during stair climbing and subdivide the stair climbing gait cycle. Leg stiffness was determined as the ratio of changes in ground reaction force in the direction of the support leg ${F}_{l}$ (leg force) to the respective changes in length ${L}_{l}$ during the entire stance phase. Eight subjects ascended and descended an instrumented staircase at different cadences. In this study, the changes of leg force and length (force–length curve) are described as the leg stiffness curve, the slope of which represents the normalized stiffness during stair climbing. The stair ascent and descent gait cycles were subdivided based on the negative and positive work fluctuations of the center-of-mass (CoM) work rate curve and the characteristics of leg stiffness. We found that the leg stiffness curve consists of several segments in which the force–length relationship was similarly linear and the stiffness value was relatively constant; the phase divided by the leg stiffness curve corresponds to the phase divided by the CoM work rate curve. The results of this study may guide biomimetic control strategies for a wearable lower-extremity robot for the entire stance phase during stair climbing.